An improved heat transfer and fluid flow model of wire-arc additive manufacturing. (March 2021) - Ou, W.; Knapp, G.L.; Mukherjee, T.; Wei, Y.; DebRoy, T.
Highlights: We develop & test a mechanistic model of multi-track wire arc additive manufacturing 3D transient model considers mass addition, heat transfer, fluid flow & free surface Computational speed is significantly enhanced by using an adaptive meshing Arc pressure and fluid flow are dominant factors in determining deposit geometry Important model predictions for H13 steel and Ti-6Al-4V are validated with data Abstract: Wire-arc additive manufacturing provides the fastest metal printing rate among all printing processes. Heat transfer and fluid flow models offer a usable connection between process variables and the parameters that affect the structure and properties of parts. Here we develop a computationally efficient, three-dimensional, transient, heat transfer and fluid flow model to calculate temperature and velocity fields, deposit geometry, cooling rates, and solidification parameters that affect the microstructure, properties, and defect formation. Calculations are done for multi-track depositions of a tool steel H13 and a titanium alloy Ti-6Al-4V and the computed results are tested using experimental data for different processing conditions. It is found that convective flow and arc pressure are the two most important factors that govern the width and depth of penetration, respectively. An adaptive grid technique proposed here enhances the computational speed by as much as by 50% without affecting the accuracy of the computed results. For the same processing conditions, Ti-6Al-4V exhibits a larger fusion zone than that for H13 steel attributed to the lower density of Ti-6Al-4V. In addition, Ti-6Al-4V exhibits faster cooling rates during solidification than H13 steel because of the lower difference between the liquidus and solidus temperatures for Ti-6Al-4V. A smaller hatch spacing results in a larger pool and slower cooling rates during the solidification of both alloys.